PENGEMBANGAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA SEKOLAH DASAR PADA MATERI PREPOSITIONS OF PLACE - Siti Fudiana; imamudin; Lira Erwinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skill is an important productive competency in English language learning at the elementary school level, yet many students still demonstrate low proficiency in this area. This study aims to describe students' speaking skills on the Prepositions of Place material before and after applying the Total Physical Response (TPR) method, analyze its effectiveness, and statistically prove its influence. The study employed a quantitative approach with a One Group Pretest-Posttest Design involving 30 third-grade students at SDN Cilegon 10. Data were collected through speaking tests covering pronunciation, vocabulary, grammar, fluency, and self-confidence. Results showed the mean score increased from 56.13 (pretest) to 78.63 (posttest). The Paired Sample t-test yielded t = -24.306 with sig. = 0.000 (< 0.05), confirming a significant effect. The N-Gain test yielded an average of 0.53 in the moderate category. Thus, students' speaking skills on Prepositions of Place material improved significantly through the application of the TPR method.